Strategies of the Cirebon City Department of Culture and Tourism to Address the Younger Generation’s Lack of Interest in Local Culture - Firman Fathurrahman; Siti Khumayah (Journal Customary Law, 2026)
Local culture is an important part of a region’s identity that must be preserved, especially amid the growing tide of globalization. The spread of globalization and the influx of foreign cultures can influence the lifestyles of the younger generation, which in turn leads to a decline in interest in local culture. This phenomenon is also occurring in the city of Cirebon, where young people aged 20–25 currently show little interest in local cultures such as sintren or tarling and prefer foreign cultures like K-Pop. The purpose of this study is to analyze the strategies and effectiveness of policies implemented by the Cirebon City Department of Culture and Tourism in addressing the low interest among young people in this age group. This study employs a qualitative approach using descriptive methods. The analysis is based on policy effectiveness theory. The results indicate that the policies implemented by the department have had a positive impact, as many young people are now interested in learning about local culture; however, several challenges remain, such as budget constraints and the strong influence of foreign culture on the younger generation. The conclusion of this study indicates that the strategies implemented have yielded positive results in increasing the younger generation’s interest in local culture; however, digital-based policy innovations and stronger collaboration with the younger generation are needed so that efforts to preserve local culture can be carried out more effectively.